Pengaruh Kualitas Audit dan Independensi Komite Audit terhadap Kualitas Pelaporan Keuangan di Sektor Kesehatan - Andini Andini; Rahman Anshari; Muhammad Iqbal Pribadi (BADAN PENERBIT STIEPARI PRESS, 2025)
Purpose. This study aims to determine the influence of audit quality and audit committee independence on the quality of financial reporting in the health sector. Method. This research is a quantitative study with a population in the form of health sector companies listed on the IDX for the period 2014–2023. The sample was selected through the purposive sampling method and obtained 106 companies that met the criteria, namely publishing annual reports and financial statements in rupiah. Data containing indications of negative profit management were excluded from the observation. Data analysis was carried out using multiple linear regression, hypothesis test, classical assumption test, and descriptive statistics. Result. In the test results, it was found that audit quality had a positive effect on the quality of financial reporting, and the independence of the audit committee did not have a significant effect on the quality of financial reporting. Implication. Provide input for companies in improving the quality of financial reporting through improving audit quality. For stakeholders and regulators, this study highlights the limited role of audit committee independence without further strengthening of governance mechanisms.